Evidence for a synergistic effect of NPY1R agonist co-administered with Ketamine in rats: relevance to neurodegenerative and mood disorders. - Moreno-Madrid, Isabel; Arrabal-Gómez, José Carlos; Díaz-Sánchez, Estela; Álvarez-Contino, José Erik; Barbancho-Fernández, Miguel Ángel; Sánchez-Pérez, José Andrés; Blanco-Reina, Encarnación; Beltrán-Casanueva, Rasiel; Hernández-García, Aracelis; Bayolo-Guanche, Juan Vicente; Romero-Imbroda, Jesús; Fuxe, Kjell; et al. (My University, 2024)
Introduction/Objetives: Major depressive disorder is one of the most prevalent health problems worldwide and its current therapeutic approach still generates great dissatisfaction due to its limited efficacy, unwanted side effects and delays in effectiveness. This research addresses the problem by studying the combined effect of co-administration of Neuropeptide Y1R (NPY1R) and Ketamine on its neurobiological action in the hippocampus and its implications on cognition and mood-related behaviours. Materials and methods: In the protocol used, the NPY1R agonist is administered intranasally together with ketamine intraperitoneally in adult Sprague-Dawley rats. Mood-related behaviours were assessed with the Forced Swimming Test (FST), while the object-in-place task was used for spatial memory. To examine markers of neurogenesis, in situ Proximity Ligation Assay, Immunohistochemistry for PCNA, DCX, BDNF and NPY1R/TrkB heteroreceptor complexes were performed in the hippocampus. Results: Increased formation of NPY1R/TrkB heteroreceptor complexes and the presence of BDNF following co-administration has been found to be associated with improved memory consolidation, increased neuroblast proliferation and correlates with decreased immobility in the FST . Conclusion: The formation of NPY1R/TrkB heteroreceptor complexes in the hippocampus by the synergistic effect of co-administration of NPY1R and Ketamine, improves cognitive functions, enhances the antidepressant effect, induces TrkB signalling and hippocampal neurogenesis. These findings open new therapeutic avenues for the treatment of neurodegenerative and mood disorders.
Keywords: Neurobiología del desarrollo; Sistema nervioso - Degeneración; Neuropéptidos; Ketamina; Modelos animales en investigación; Neurogenesis; Neurodegenerative and mood disorders; Neuropeptide Y1R ketamine interaction